Habitar a Rua: O efémero - Apropriação de outros espaços do esquecimento - Marta Sofia Lopes Regadas (2021)
This dissertation aims to research an urban phenomenon: a type of urbanistic appropriation carried out by groups of citizens experiencing homelessness. According to the National Statistical Institute of Portugal (INE), someone is considered to be experiencing homelessness when, in the moment of the census, they are found to be "living in the street or other public space, such as gardens, underground stations, bus stops, bridges, flyovers and arcades, among others, or forced to spend most hours of the day in a public space, despite sleeping at a shelter". In the city of Porto, there are currently 286 people recorded as experiencing homeless. These are people struggling for survival, deprived of their right to housing. The city is fraught with emptiness, spaces belonging to nobody, from public areas to private buildings, and these have been progressively appropriated by those without access to a permanent personal place. The aim here is then to shine a light on this peculiar form of inhabiting a city, on these people's lives and their ephemeral appropriations. The dissertation takes as its point of departure a reflection on the present social role of the architect, seeking simultaneously to bridge multidisciplinary knowledge, and posing collaborative work as a means of raising awareness and carrying out direct intervention. At its heart is a critical questioning about this alternative practice to housing policies, which has seen an escalation in the last decade. This demands a research into the invisibility linked with the condition of homelessness, and how this difficulty casts doubt over the possibility of a solution. More than aiming to solve such a complex issue, a contribution is sought to be offered by amplifying the voices of those who are so seldom heard. This can only be achieved by acknowledging the vulnerability of these communities, and demystifying the stigma around those who live in the street - from the erroneous association with criminality to the fallacy of a "purported choice".